Metal-organic framework-encapsulated dihydroartemisinin nanoparticles induces apoptotic cell death in ovarian cancer by blocking ROMO1-mediated ROS production - Yuanliang Yan; Xiaoxin Yang; Ning Han; Yuanhong Liu; Qiuju Liang; Liu-Gen Li; Jun Hu; Tong-Fei Li; Zhijie Xu (Journal of Nanobiotechnology, 2023)
Abstract Dihydroartemisinin (DHA), a natural product derived from the herbal medicine Artemisia annua, is recently used as a novel anti-cancer agent. However, some intrinsic disadvantages limit its potential for clinical management of cancer patients, such as poor water solubility and low bioavailability. Nowadays, the nanoscale drug delivery system emerges as a hopeful platform for improve the anti-cancer treatment. Accordingly, a metal-organic framework (MOF) based on zeolitic imidazolate framework-8 was designed and synthesized to carry DHA in the core (ZIF-DHA). Contrast with free DHA, these prepared ZIF-DHA nanoparticles (NPs) displayed preferable anti-tumor therapeutic activity in several ovarian cancer cells accompanied with suppressed production of cellular reactive oxygen species (ROS) and induced apoptotic cell death. 4D-FastDIA-based mass spectrometry technology indicated that down-regulated reactive oxygen species modulator 1 (ROMO1) might be regarded as potential therapeutic targets for ZIF-DHA NPs. Overexpression of ROMO1 in ovarian cancer cells significantly reversed the cellular ROS-generation induced by ZIF-DHA, as well as the pro-apoptosis effects. Taken together, our study elucidated and highlighted the potential of zeolitic imidazolate framework-8-based MOF to improve the activity of DHA to treat ovarian cancer. Our findings suggested that these prepared ZIF-DHA NPs could be an attractive therapeutic strategy for ovarian cancer.